Pengaruh Profitabilitas pada Manajemen Laba Sektor Real Estate 2021-2022 - Sadzili, Rohan As; Suhartini, Dwi (Universitas Multi Data Palembang, 2025)
This study aims to analyse the effect of profitability on earnings management in the real estate and property sector in Indonesia during the 2021-2022 period. Using a quantitative method with a sample of 100 companies listed on the Indonesia Stock Exchange (IDX), this study measures earnings management through discretionary accruals with the Jones Modified model, while profitability is measured using Return on Assets (ROA). Hypothesis testing results show that profitability has no significant effect on earnings management, although 68% of companies engage in the practice. Descriptive analysis reveals extreme variations in earnings management, while profitability is relatively stable. Based on Agency Theory, conflict of interest between management and shareholders and information asymmetry are the dominant factors. The implications of the study emphasise the importance of close supervision, improved corporate governance, and transparency of financial statements to reduce the risk of manipulation. The findings provide insights for regulators and stakeholders in optimising sectoral accounting policies.